Estimation of survival functions in interval and right censored data using STD behavioural diaries - Harezlak, Jaroslaw (2006)
In investigations of sexually transmitted diseases (STDs), true infection times are often either interval censored or right censored. For such data, reliable estimation of the survival function is difficult to obtain. In this research, we propose a resampling based method for the estimation of the survival function using auxiliary behavioural information provided by daily diaries. By imputing the unknown infection time from a list of sexual encounter times recorded in the diaries, the proposed procedure can be easily implemented using existing estimation procedures for right censored data. Our simulations show that the proposed procedure consistently outperforms the existing ad hoc estimation methods and produces smaller mean integrated squared errors (MISE). We illustrate this method by analysing infection data obtained from an ongoing STD investigation of adolescent females.